Dinamismo lexical nas redes sociais: Contribuições para a Lexicografia - De Carvalho Bertonha, Fábio Henrique [UNESP]; Zavaglia, Claudia [UNESP] (UNISINOS - Universidade do Vale do Rio Dos Sinos, 2017)
This paper proposes a reflection on the (internal and external) lexical dynamism, including social networks, in order to discuss its contributions to Lexicography, as the lexicon of a language system is supported by its constant evolution. To meet this purpose, theoretical postulations from Lexicography and Semantics are introduced, as well as contributions from Pragmatics and Terminography. These are used to support discussions based on some lexical items found in the most updated dictionaries of Brazilian Portuguese language, such as Ferreira (2010) and Houaiss (2009); of Italian language, as Zingarelli (2016); and of English language, as Oxford (2015, 2016). New entries and new meanings found in these lexicographical works are discussed in terms of the influence of media and social networks. Their inclusion into the Brazilian, Italian and English linguistic systems are analyzed through examples of some lexemes, whose tendency is the increase of the lexical flow. The advance of technology was found to contribute to the exponential increase of the lexicon, particularly through social networks, which connect, at the same time, a wide range of native speakers and foreign users to the same environment. Lexicography could consider this recent technological reality in order to register these lexical items in the dictionary as they are created and disseminated; obviously, they would be subjected to inclusion criteria justified theoretically.
Lexical dynamism in social networks: Contributions to Lexicography
Keywords: Lexical dynamism; Lexicon; Social networks